Pemberdayaan Siswa SMA di Kota Pariaman Melalui Aksi Promotif Kefarmasian (Apotek-R) sebagai Upaya Pencegahan terhadap Kejahatan Narkoba - Syofyan Syofyan; Erizal Erizal; Suryati Suryati (Warta Pengabdian Andalas, 2019)
Drug abuse has been so alarming that victims of both young and adult children always fall every day and tend to increase from year to year. Various strategies have been carried out by the government to eradicate this drug crime, including preventive efforts to schools. Pariaman City as a crossing area in West Sumatra is a place that is prone to this drug crime. To that end, in an effort to prevent the occurrence of drug crimes, especially for high school students in Pariaman City, activities have been carried out in the form of pharmaceutical promotive actions (Apotek-R). The purpose of this activity is to know the description of the knowledge of high school students in Pariaman City, about Drugs and the influence of the Apotek-R activities on the prevention of drug abuse. The method used in the form of Communication, Information and Education (CIE) uses a pharmacy promotion action (Apotek-R). From this activity information was obtained that the knowledge of high school students in Pariaman City about drug problems is quite good. Promotional action activities of pharmacy (Apotek-R) can be used as a model in providing positive activities in efforts to prevent drug abuse among high school students.